2010
DOI: 10.1248/bpb.33.1070
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Effects of Docosahexaenoic Acid against Various Pain Stimuli in Mice

Abstract: Docosahexaenoic acid (DHA), an omega-3 polyunsaturated fatty acid (n-3 PUFAs), is an essential polyunsaturated fatty acid in the central nervous system, and possesses many physiological functions in neurodegenerative diseases. Previously, there are some reports that n-3 PUFAs contribute to pain relief. As the antinociceptive effect of DHA alone has not been reported, this study examined the antinociceptive effect of DHA on various pain stimuli. To evaluate the antinociceptive effect of DHA on thermal and chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 26 publications
5
54
0
Order By: Relevance
“…29) DHA is also found in the heart as well as in sperm and breast milk. 30) We have proposed the possible involvement of DHA in pain control because of its dose-dependent antinociceptive effects observed in various pain tests 31) and its calming effect on neuropathic pain (Fig. 3).…”
Section: N-3 Pufas and Painmentioning
confidence: 99%
“…29) DHA is also found in the heart as well as in sperm and breast milk. 30) We have proposed the possible involvement of DHA in pain control because of its dose-dependent antinociceptive effects observed in various pain tests 31) and its calming effect on neuropathic pain (Fig. 3).…”
Section: N-3 Pufas and Painmentioning
confidence: 99%
“…Stabilizing cell membrane structures in the central and peripheral nervous systems and reduction of pro-inflammatory cytokines synthesis in damaged tissue can be considered a mechanism of antiinflamatory and therefore analgetic action of DHA (Cunnane et al, 2009;Bousquet et al, 2009). To date, these effects have been described in animal pain models (Nakamoto and Nishinaka, 2010;Dyuizen et al, 2013) and during some clinical trials (Goldberg and Katz, 2007). The anti-inflammatory action of DHA and its direct effects on prostaglandin production, leukocyte proliferation and cell migration to the damaged tissue can explain its analgetic activity in some painful neurological injuries.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory action of DHA and its direct effects on prostaglandin production, leukocyte proliferation and cell migration to the damaged tissue can explain its analgetic activity in some painful neurological injuries. It is possible that the antinociceptive effect of DHA may be partly due to attenuation of the central sensitization induced by some inflammatory substances (Nakamoto and Nishinaka, 2010). Besides, DHA might relieve the pain, by modulating the local inflammatory and necrobiotic processes within the central nervous system in the foci of neural tissue damage due to the trauma or denervation (Bazan, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The enteral DHA administration can reduce inflammatory mediators in patients who undergo major surgery [16] , which are also inducers of pain [18] . Experimental models have demonstrated that DHA ameliorates acute pain related to acute inflammation [19,20,31] . Hence, DHA might be a relevant approach in this vulnerable population who cannot express displeasure as a result of being exposed repeatedly to painful stimuli with long-term adverse effects such as retaining a lifetime pain memory, decreasing their pain threshold, among others.…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant because pro-inflammatory cytokines IL-1β, IL-6 and tumor necrosis factor-α (TNF-α) induce pain and hyperalgesia [18] . Moreover, studies in animal models have also demonstrated the capacity of DHA to reduce acute pain associated with inflammation, attenuating or modifying lipidderived inflammatory mediators [19][20][21] , but studies in humans are lacking.…”
Section: Introductionmentioning
confidence: 99%